Efeito dos parâmetros de insensibilização de aves segundo o regulamento europeu 1099/2009 na qualidade da carne - Rocha, Bruna Regina Pereira da (2021)
The consumption of poultry meat is significantly high worldwide and before slaughter, poultry are stunned in order to promote unconsciousness and absence of pain in the animal. Brazilian exports to the European market use electronarcosis as a stunning method. The aim of this work was to evaluate the effect of stunning parameters based on EC Regulation 1099/2009 using the variables frequency and duty cycle (duty cycle). Nine trials were conducted, whose variable responses were based on the indicators of stunning animals and meat quality. The frequencies evaluated (700 Hz, 1100 Hz and 1500 Hz) showed a higher incidence of voluntary blinking, arched neck and wing fracture, indicating that the poultry were not adequately stunned. On the other hand, for these indicators of Animal Welfare (BEA), the duty cycle at the intensity of 25% and 40% promoted the stunning of poultry. The interaction of the 1100 Hz frequency with the 15% duty cycle resulted in a higher incidence of arched neck and the 1500 Hz frequency with the 40% duty cycle increased the incidence of wing fractures. There was no significant difference for 24h pH values, bruises between breast and wing and drip loss for all evaluated treatments. For color (a* and b*) a significant influence can be observed in the higher frequencies, which showed a pale color. For pH 2h, the assays evaluated showed a significant influence, however, all means observed were higher than the pH considered normal for poultry meat (between 5.7 and 5.9). For shear strength, it was observed that the highest frequencies and the interaction of the 1500 Hz frequency with the 15% and 25% duty cycle had the highest values for this indicator, demonstrating greater difficulty in breaking muscle fibers. For water holding capacity, the frequency of 1100 Hz in isolation and, associated with the 25% duty cycle, presented the highest values for this indicator, demonstrating a greater exudation in these conditions and, therefore, a lower water holding capacity. Therefore, all tests resulted in some level of impairment of the indicators, except for the variable duty cycle 40%, which showed a positive influence on the indicators evaluated. Duty cycle interference must be considered in order to develop combinations at other configuration levels that favor positive conditions for applicability in the industry.